Implementasi Media Pembelajaran Permainan Monopoli untuk Meningkatkan Minat Belajar Peserta Didik pada Mata Pelajaran Pendidikan Pancasila - Ulfa, Lina Zumrotul; Rofiki, Imam (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2025)
This research aims to implement monopoly game learning media on the material of applying Pancasila values ​​in increasing interest in learning. Class 5B students at Anak Saleh Elementary School. The method used is research and development (R&D). The R&D development model is the ADDIE model, namely Analysis, Design, Development, Implementation and Evaluation. The results of this research show that students in class 5B have high interest in learning as seen from the students' activeness in playing, the students' activeness in answering questions, the cooperation carried out to answer questions so that they better understand the application of Pancasila values ​​in everyday life through this game